PENERAPAN STRATEGI THE FIRING LINE UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA SMP - Selvia Lovita Sari; Rubhan Masykur; Rizki Wahyu Yunian Putra (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The objective in this research is to find out whether the ability to understand student’s mathematical concepts with the application of The Firing Line strategy is better than ordinary learning. This research used quantitative research. The method used quasi experiment using pretest- posttest Control Group Design. The population in this study is all students in class VIII SMPN 3 Jati Agung. Sampling used class random technique by lottery technique, obtained class VIII A as experiment class and class VIII B as control class. Based on the results of the N-gain hypothesis test the ability to understand mathematical concepts in the material builds up a flat side space (cubes and beams) at signification level obtained value and . Because . Its means is rejected. Thus, it can be concluded that the ability to understand student’s mathematical concepts with The Firing Line strategy is better than ordinary learning models.